Great nation vs. great country : South Korea and Brazil following different pathways - Tumolo Neto, Roque João (2022)
Tese (doutorado) — Universidade de Brasília, Instituto de Ciências Sociais, Departamento de Estudos Latino-Americanos, Programa de Pós-Graduação em Estudos Comparados sobre as Américas, 2022.